The UK’s Prevent policy as a form of risk governance in the education sector and how it violates human rights and fundamental freedoms - Wainaina, Beatrice Wambui (Kent Law Review, 2018)
The UK’s Prevent Program within the education sector and its referral initiative Channel, are counter-effective. The government claims that these initiatives are a means of safeguarding vulnerable students from extremism. Contrary to these claims is that the Prevent program is not well received within the education sector. In fact, most interactions that have involved police intervention have resulted in violations of human rights and fundamental freedoms of children under the care act. Consequently, a number of lawsuits have been levied against Prevent by parents and academicians which is highlighted in this paper. Furthermore, the statutory duty imposed under Prevent is a form of risk governance driven by pre-emption. British Muslim students are singled out as suspect communities because they ‘lack in Britishness’ and placed under surveillance. Moreover, the government claims that Prevent is a safeguarding initiative implemented to protect vulnerable students from extremism. This paper will show that the uncertainty level presented by the term extremism, renders Prevent’s risk assessment unreliable. Furthermore, the changing level of risk associated with risk governance renders the premise of Prevent political. This is the kind of governmentality that is constructed at the supranational level and implemented locally through domestic policies such as Prevent.